From Socialism to Market Economy: The Transition Period - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "From socialism to market economy: the transition period," edited by William S. Kern.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; economic development